COVID‐19 screening test by using random oropharyngeal saliva. Issue 4 (22nd January 2021) - Rao, Mohan; Rashid, Fairuz A.; Sabri, Fashihah S. A. H.; Jamil, Nur Nadia; Seradja, Valentinus; Abdullah, Nurul A.; Ahmad, Hanisah; Aren, S. L.; Ali, Shareh A. S.; Ghazali, Mawaddah; Manaf, Anizan A.; Talib, Harishah; et al.
Abstract: An optimal clinical specimen for accurate detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) by minimizing the usage of consumables and reduce hazard exposure to healthcare workers is an urgent priority. The diagnostic performance of SARS‐CoV‐2 detection between healthcare worker‐collected nasopharyngeal and oropharyngeal (NP + OP) swabs and patient performed self‐collected random saliva was assessed. Paired NP + OP swabs and random saliva were collected and processed within 48 h of specimen collection from two cohort studies which recruited 562 asymptomatic adult candidates. Real‐time reverse‐transcription polymerase chain reaction targeting Open reading frame 1a (ORF1a) and nucleocapsid (N) genes was performed and the results were compared. Overall, 65 of 562 (28.1%) candidates tested positive for COVID‐19 based on random saliva, NP + OP swabs, or both testing techniques. The detection rate of SARS‐CoV‐2 was higher in random saliva compared to NP + OP testing (92.3%; 60/65 vs. 73.8%; 48/65; p  < .05). The estimated sensitivity and specificity of random saliva were higher than NP + OP swabs (95.0; 99.9 vs. 72.2; 99.4). The C t  values of ORF1a and N genes were significantly lower in random saliva compared to NP + OP swabs specimens. Our findings demonstrate that random saliva is an alternative diagnostic specimen for the detection of SARS‐CoV‐2. Self‐collected random oropharyngeal saliva is a valuable specimen that provides accurate SARS‐CoV‐2 surveillance testing of a community.